2020
DOI: 10.2217/imt-2019-0108
|View full text |Cite
|
Sign up to set email alerts
|

5 Years of Clinical DC-CIK/NK Cells Immunotherapy for Acute Myeloid Leukemia â€“ a Summary

Abstract: Aim: To assess the efficacy of dendritic cells-cytokine induced killer (DC-CIK) and natural killer (NK) cell-based immunotherapy in treating the low- and intermediate-risk acute myeloid leukemia. Patients & methods: DC-CIK or NK cells were infused once every 3 months for 2–4 cycles to 85 patients. Results & conclusion: The 5-year overall survival (OS) and relapse-free survival (RFS) rates were 90.5 and 65.2%, respectively. The OS of the very favorable, the favorable and the intermediate-risk groups was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…There is a significant pathophysiological difference between the cancer of the two subjects, specifically the contrast between solid and liquid cancers. Both the solid and liquid cancer subjects in this trial experienced positive outcomes in their overall cancer treatment, echoing results demonstrated by previous research in both groups ( 9 , 11 , 13 , 14 ). Notably, in this trial and in numerous other aforementioned systematic reviews and meta-analyses of DC-CIK clinical trials, there have been no severe adverse effects reported related to the DC-CIK immunotherapy.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…There is a significant pathophysiological difference between the cancer of the two subjects, specifically the contrast between solid and liquid cancers. Both the solid and liquid cancer subjects in this trial experienced positive outcomes in their overall cancer treatment, echoing results demonstrated by previous research in both groups ( 9 , 11 , 13 , 14 ). Notably, in this trial and in numerous other aforementioned systematic reviews and meta-analyses of DC-CIK clinical trials, there have been no severe adverse effects reported related to the DC-CIK immunotherapy.…”
Section: Discussionsupporting
confidence: 86%
“…As far as we are aware, this is the first report of DC-CIK therapy for CLL and peritoneal cancer, respectively. The use of DC-CIK as an adjunct to standard cancer treatments has piqued the interest of oncologists due to convincing results reported by preclinical and clinical trials in several different cancer types (9,(11)(12)(13)(14). Research investigating a combination of DC-CIK immunotherapy and chemotherapy in different cancer types has revealed significant variations in cell dosage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that DC's may actually mediate immune tolerance and therefore allow disease progression [93]. There is a huge opportunity to exploit DC heterogeneity for immune therapy, and current trials include the production of DC vaccines [94,95] and the combination of DCs with cytokine-induced killer cells or DC-CIK therapy [96,97].…”
Section: Novel Immune Cell Targetsmentioning
confidence: 99%
“…In addition, Tregs inhibit the differentiation of B cells through the granzyme A pathway [ 21 ]. In immunotherapy for leukemia, dendritic cells cytokine induced killer cell (DC-CIK) loaded with specific leukemia cells significantly decreases the peripheral Treg distribution in patients with ALL [ 22 ]. Although the immunosuppressive and tumor-promoting effects of Tregs in the occurrence and development of ALL in children have been gradually clarified by researchers, the effects of the promotion of Treg differentiation on the occurrence of ALL in children, as well as the specific upstream regulatory mechanism, remain unclear.…”
Section: Introductionmentioning
confidence: 99%